Processing and characterization of biobased polymer derived from Tacca leontopetaloides starch with rice husk silica and natural rubber blends / Nurul Shuhada Mohd Makhtar - Mohd Makhtar, Nurul Shuhada (2015)
The non-renewable source of petroleum based plastic such as Polyethylene (PE), calls for a need to look into this natural based polymer. Polylactic acid (PLA) is the promising synthetic polymer which is derived from the natural monomer lactic acid extracted from starch such as com starch; whereby need to compete as a staple food. Therefore, in this research, new source of starch called Tacca leontopetaloides is introduced, which has potential to be utilized as raw material to produce biopolymer such as bio-thermoplastic elastomers. The incorporated plasticized Tacca starch and matrix natural rubber filled with silica from rice husk and sulphur vulcanization by using two roll-mill machine is producing a bio-thermoplastic elastomer. The chemical, thermal and mechanical study was done on two formulations, firstly to evaluate the effect of volume plasticizers and secondly to study the effect of natural rubber and glycerol ratio in the blending process. The best mechanical and thermal characteristic was then compared with PE/NR/Silica and PLA/NR/Silica blends as a standard TPE. Among the TPEs, TPE 15 with 50:6 natural rubber to glycerol ratio had showed higher tensile strength at 1.467 MPa and elongation at break at 265 mm with higher thermal resistant leaving 24.8 % amount of residue at 500 °C. This property is highly achieved the minimum tensile needed for floor mat production at 0.294 MPa with minimum elongation at 200 mm. Based on this, Tacca leontopetaloides starch plasticized with glycerol and filled with silica rice husk has the capability to replace synthetic raw material used in producing bio-thermoplastic elastomer floor mat for car industry.